An innovative approach for automatic generation, verification and optimization of part programs in turning. (July 2015) - Sortino, M.; Belfio, S.; Totis, G.
Abstract : Graphical abstract: Abstract : Highlights: Automatic approach for generation, verification and optimization of part programs. Simulation of generic turning operations of any axial symmetrical geometry. Simulation of cutting forces, deformations, tool wear, workpiece accuracy. Analysis of complex machining cost function behavior. Innovative gradient-descent optimization approach. Abstract: Continuous innovation of products and optimization of manufacturing processes are of fundamental importance for preserving competitiveness. In the last decades, several approaches based on analytic models for optimization of basic machining operations such as cylindrical turning and face milling have been developed. However, the analytic approaches may not be adequate for real industrial applications, since they are based on average cutting parameters and thus they are not capable of taking into account the effect of complex geometries and instantaneous cutting conditions. In this paper, an innovative integrated system for automatic generation of optimized part programs in turning based on realistic machining simulation is proposed. The system components are described in detail and the machining simulator is validated by comparison with the results of real cutting tests. Then, the optimization approach is applied to a simple case study. The results show that the behavior of the cost function is rather complex, even for simple workpieces. Moreover, the simulator can detect unfeasible combinations of cutting parameters and thus reduce inline part program refinement and optimization. The optimal combination of cutting parameters determined by the new system was competitive with the solutions derived from tool specifications or proposed by a machining expert.